Comprehensive analysis for detecting radiation-specific molecules expressed during radiation-induced rat thyroid carcinogenesis. (5th May 2021) - Kurohama, Hirokazu; Matsuda, Katsuya; Kishino, Mio; Yoshino, Miruki; Yamaguchi, Yuka; Matsuu-Matsuyama, Mutsumi; Kondo, Hisayoshi; Mitsutake, Norisato; Kinoshita, Akira; Yoshiura, Ko-ichiro; Nakashima, Masahiro
ABSTRACT: Although the association between radiation exposure and thyroid carcinogenesis is epidemiologically evident, 'true' radiation-induced cancers cannot be identified from biological evidence of radiation-associated cases. To assess the individual risk for thyroid cancer due to radiation exposure, we aimed to identify biomarkers that are specifically altered during thyroid carcinogenesis after irradiation in a time-dependent manner in an animal model. Thyroid glands were obtained from rats ( n  = 175) at 6–16 months after local X-ray (0.1–4 Gy) irradiation of the neck at 7 weeks of age. The gene expression profile in thyroid glands was comprehensively analyzed using RNA microarray. Subsequently, the expression levels of the genes of interest were verified using droplet digital PCR (ddPCR). The expression level of candidate genes as biomarkers for irradiated thyroid was examined in a randomized, controlled, double-blind validation study ( n  = 19) using ddPCR. The incidence of thyroid cancer increased in a dose- and time-dependent manner and was 33% at 16 months after irradiation with 4 Gy. The Ki-67 labeling index in non-tumorous thyroid was significantly higher in the exposed group than in the control. Comprehensive analysis identified radiation-dependent alteration in 3329 genes. Among them, ddPCR revealed a stepwise increase in CDKN1A expression from early pre-cancerous phase in irradiated thyroid compared to that in the control. The irradiated thyroids were accurately distinguished (positive predictive value 100%, negative predictive value 69%) using 11.69 as the cut-off value for CDKN1A/β-actin . Thus, CDKN1A expression can be used as a biomarker for irradiated thyroid glands at the pre-cancerous phase.